A method for preparing nickel-cobalt nanowire electrode material

By introducing an AC magnetic field at a specific temperature, a nickel-cobalt nanowire electrode material with high electrolyte wetting and magnetic separation characteristics was prepared, which solved the problem of poor electrochemical performance caused by irregular structure of the existing electrode material, and achieved high Mass load and long-life electrode material.

CN119035569BActive Publication Date: 2025-02-25JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411506878.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-25
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The microstructure arrangement of existing supercapacitor electrode materials is not orderly enough, resulting in poor electrochemical performance, poor electrolyte wetting ability and insufficient electrode active sites, which limits the application effect and life of the material.

Method used

By introducing an AC magnetic field at a specific temperature and reducing the nickel-cobalt metal salt with NaBH4, a nickel-cobalt nanowire electrode material with high electrolyte wetting and magnetic separation characteristics was prepared.

Benefits of technology

The high-quality loading and orderly arrangement of nickel-cobalt nanowire electrode materials are achieved, which significantly improves the wettability and electrochemical properties of the electrolyte and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119035569B_ABST
    Figure CN119035569B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a nickel-cobalt nanowire electrode material capable of achieving high mass loading, belonging to the technical field of supercapacitor electrode materials. The method comprises: 2 6H 2 O and CoCl 2 6H 2 O was dissolved in deionized water and then dispersed by ultrasonic and mixed with the prepared NaBH 4 The solutions are mixed, reacted under an external AC magnetic field and a certain temperature, and then a black powder sample is obtained by magnetic separation technology. Finally, after washing and drying, a nickel-cobalt nanowire electrode material with high mass loading is obtained. The preparation method of the present invention is simple to operate. By dynamically adjusting the direction and intensity of the magnetic field, the arrangement of the nanowires can be precisely controlled, making the synthesized nanowire structure more uniform and regular, reducing the curvature of the material, and thus significantly improving the wettability of the electrolyte. The material we prepared has a mass loading of 10 mg cm ‑2 It still has excellent electrochemical properties, and is further moving towards electrode materials that meet the needs of actual production and industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of supercapacitor electrode materials, and specifically relates to a nickel-cobalt nanowire electrode material and a preparation method thereof. Background Art

[0002] Supercapacitors, also known as electrochemical capacitors, are a new type of energy storage element. Because of their advantages such as good rate performance, fast charging and discharging speed, long service life and safety, they have great development potential and application value in the fields of electronics, transportation, information, etc. The performance and working state of supercapacitors depend to a large extent on the microstructure of the electrode material. However, the microstructure arrangement of most electrode materials is not orderly enough and is still in a "low" state: low mass loading or low specific capacity. In general, many pseudocapacitive materials, especially transition metal composites, exhibit a charge storage process dominated by surface / interface redox reactions, thus providing a high theoretical capacity. At present, using NaBH 4 The method of reducing metal salts to generate nanomaterials has been widely studied and applied because of its relative simplicity, low cost and easy operation.

[0003] In the prior art, Zhao et al. [Journal of Alloys and Compounds, 2021, 850] used NaBH 4 The capacity of the synthesized ternary nickel-cobalt-iron compound can only reach 1317 F g by reducing nickel metal salt without considering the reaction temperature. -1 , and even at relatively low loadings (2 mg cm -2 ). Many studies have shown that temperature changes can significantly affect reaction kinetics, which in turn has an important impact on the crystal structure and morphology of the material, but these factors are often not fully considered in traditional methods. Guo et al. [Chemical communications (Cambridge, England), 2021, 57(73): 9216-9219.] synthesized electrode materials under the action of a 0.15 T magnetic field induced by two NdFeB magnets. However, this method has obvious limitations, mainly reflected in the fact that the microstructure of the generated nanomaterials is not orderly enough, which directly affects the performance of the material, especially the electrochemical performance when used as an electrode material.

[0004] Therefore, on the one hand, current research and applications are mainly concentrated under room temperature conditions, ignoring the profound impact of temperature on the stability and quality of nanomaterials during synthesis; on the other hand, in terms of material structure control, traditional methods usually use a single vertical magnetic field to control the arrangement of nanomaterials, and the resulting nanomaterial microstructure is not orderly enough. This irregular structure easily leads to poor electrolyte wettability, low electrical conductivity and insufficient electrode active sites, which seriously restricts the effect and life of electrode materials in practical applications. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a nickel-cobalt nanowire electrode material capable of achieving high mass loading and a preparation method thereof. In particular, by introducing an alternating magnetic field, a nickel-cobalt nanowire electrode material with high electrolyte wettability and magnetic separation properties is synthesized at a specific temperature.

[0006] In order to achieve the above technical objectives, the present invention provides the following technical solutions:

[0007] A method for preparing a nickel-cobalt nanowire electrode material is provided, comprising the following steps:

[0008] Step S1: NiCl 2 6H 2 O and CoCl 2 6H 2 O was dissolved in deionized water and ultrasonically dispersed for 5 min to form a uniform solution A;

[0009] Step S2: Prepare 0.2-0.3 mol L -1 NaBH 4 solution, denoted as solution B;

[0010] Step S3: under the action of an alternating magnetic field, adding the solution B in step S2 to the solution A formed in step S1, and reacting at a reaction temperature of 35-45° C., and terminating the reaction after the bubbles completely disappear, to obtain a solution C;

[0011] Step S4: using a magnet to separate the solution C obtained in step S3 to obtain a black powder sample, and washing it with water and ethanol;

[0012] Step S5: vacuum drying the powder separated in step S4 to obtain a high-mass-loaded nickel-cobalt nanowire electrode material.

[0013] The NiCl in step S1 of the present invention 2 6H 2 O and CoCl 2 6H 2 The molar ratio of O is 1:1-3:1.

[0014] Furthermore, the frequency of the magnetic field in step S3 is 50-150 Hz.

[0015] Preferably, the reaction temperature in step S3 is 40°C.

[0016] Further, preferably, the frequency of the AC magnetic field in step S3 is 70 Hz.

[0017] Further, as a preference, the NiCl in step S1 2 6H 2 O and CoCl 2 6H 2 O molar ratio is 2:1.

[0018] A nickel-cobalt nanowire electrode material prepared by any of the methods described above. In step S1, the NiCl 2 6H 2 O and CoCl 2 6H 2 O molar ratio is 2:1, the reaction temperature in step S3 is 40 °C, the AC magnetic field frequency in step S3 is 70 Hz, and the electrode material has a mass loading of 10 mg cm -2 When the specific capacitance is 1500 F g -1 Above 10 A g -1 The capacity retention rate at the current density is above 70%.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] Due to the introduction of AC magnetic field, NaBH 4 Reduction reaction generates a highly ordered arrangement of nickel-cobalt nanowire electrode materials. Compared with the traditional static vertical magnetic field method, the present invention achieves precise control of nanowire arrangement by dynamically adjusting the direction and intensity of the magnetic field, overcoming the irregular structure of the traditional method. This improvement makes the synthesized nanowire structure more uniform and regular, thereby significantly improving the wettability of the electrolyte and enhancing the integrity of the electrode material in the electrochemical reaction.

[0021] In addition, the synthesized nickel-cobalt nanowire material has good magnetic properties, which allows it to be separated using a simple physical magnetic attraction method, avoiding the mechanical stress and damage that high-speed centrifugation may cause to the material structure. Compared with traditional separation methods, this magnetic separation is not only easy to operate and saves time, but also effectively protects the integrity and functionality of the nanowire material, further improving the service life and performance stability of the electrode material. In general, the present invention significantly improves the preparation quality and application effect of nickel-cobalt nanowire electrode materials by optimizing magnetic field conditions and introducing physical magnetic attraction separation technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram of a preparation process of a method for preparing an ordered arrangement of nickel-cobalt nanowire electrode materials capable of achieving high mass loading provided by an embodiment of the present invention;

[0023] Figure 2 Comparison images of the scanning electron microscope (SEM) and contact angle test synthesized with and without a magnetic field;

[0024] Figure 3 It is a constant current charge and discharge curve diagram of different current densities under the best embodiment;

[0025] Figure 4 This is a scanning electron microscope image of the synthetic material under Example 1;

[0026] Figure 5 Example 1 at 1 A g -1 Constant current charge and discharge curve diagram of current density;

[0027] Figure 6 For Example 2 at 1 A g -1 Constant current charge and discharge curve diagram of current density;

[0028] Figure 7 For Example 3 at 1 A g -1 Constant current discharge curve of current density;

[0029] Figure 8 For Example 4 at 1 A g -1 Constant current discharge curve of current density;

[0030] Fig. 9 For Example 5 at 1 A g -1 Constant current discharge curve of current density;

[0031] Fig.10 For Example 6 at 1 A g -1 Constant current charge and discharge curve diagram of current density;

[0032] Fig.11This is a scanning electron microscope image of the synthetic material in Comparative Example 1;

[0033] Fig.12 For comparative example 1 at 1 A g -1 Constant current charge and discharge curve diagram of current density;

[0034] Fig.13 This is the Brunauer-Emmett-Teller test (pore size distribution diagram) under Comparative Example 2;

[0035] Fig.14 For comparative example 1 at 1 A g -1 Constant current charge and discharge curve diagram of current density; DETAILED DESCRIPTION

[0036] The specific implementation of the present invention will be further described below in conjunction with the accompanying drawings:

[0037] Best Mode

[0038] A method for preparing an ordered arrangement of nickel-cobalt nanowire electrode materials capable of achieving high mass loading comprises the following steps: Step S1: NiCl 2 6H 2 O and CoCl 2 6H 2 O was mixed and dissolved in deionized water in a ratio of 2:1, and ultrasonically dispersed for 5 minutes to form a uniform solution A;

[0039] Step S2: Prepare 0.27 mol L -1 NaBH 4 Solution, denoted as B;

[0040] Step S3: under the action of an alternating magnetic field with a frequency of 70 Hz, solution B is added to solution A, and the reaction is carried out at a reaction temperature of 40° C. The reaction is terminated when the bubbles completely disappear;

[0041] Step S4: Separating the solution obtained in step S3 using a magnet to obtain a black powder sample, and washing it with water and ethanol;

[0042] Step S5: vacuum drying the powder separated in step S4 to obtain a nickel-cobalt nanowire electrode material that can achieve high mass loading.

[0043] Figure 1 FIG. 1 is a schematic diagram of a preparation process of a method for preparing an ordered arrangement of nickel-cobalt nanowire electrode material capable of achieving high mass loading provided by an embodiment of the present invention, wherein Figure 1 It can be seen that due to the characteristics of Ni-Co magnetic metal, it can be observed that during the synthesis process, the magnetic particles form an interconnected chain structure under the action of the magnetic field. Figure 2The scanning electron microscope (SEM) and contact angle test comparison images of synthesis with and without magnetic field show that nanoparticles accumulate in the electrode material synthesized without magnetic field, resulting in serious agglomeration. When a magnetic field is introduced during the preparation process, the originally agglomerated nanoparticles form an interconnected chain structure under the action of the external magnetic field force, which increases the orderly arrangement of the nickel-cobalt compound nanowires. In addition, the chain network has a loose and porous structure. When it is used as an electrode material for supercapacitors, this ordered and loose structure is conducive to the penetration of electrolytes and rapid charge transfer. Through the contact angle test, the electrode material synthesized without magnetic field requires 109 ms for the electrolyte to be fully penetrated, while the nickel-cobalt compound nanowire electrode only requires 14 ms for the electrolyte to be penetrated. Figure 3 It is a constant current charge and discharge curve diagram of different current densities under the best embodiment; Figure 3 It can be seen that when the mass loading reaches the commercial level of 10 mg cm -2 When the capacitance is very high (1540 F g -1 ), ultra-high rate (at 10 A g -1 It has a capacity retention rate of 70.7% at the current density. Example

[0044] The frequency of the AC magnetic field in step S3 of the best embodiment is changed to 50 Hz, and the other reaction conditions are the same as those of the best embodiment to obtain a nickel-cobalt nanowire electrode material.

[0045] Figure 4 This is a scanning electron microscope image of the synthetic material under Example 1, from Figure 4 It can be seen that as the frequency of the alternating current decreases, the intensity of the magnetic field decreases, and the microstructure of the composite electrode material is slightly stacked. -2 When the specific capacity is 902 F g -1 (like Figure 5 As shown), at 10 A g -1 The capacity retention rate is 57.2% at the current density. At the same time, through the contact angle test, the material can allow the electrolyte to fully penetrate in 53 ms. Example

[0046] The frequency of the AC magnetic field in step S3 of the best embodiment is changed to 150 Hz, and the other reaction conditions are the same as those of the best embodiment to obtain a nickel-cobalt nanowire electrode material.

[0047] As the frequency of the alternating current increases, the intensity of the magnetic field increases, and the original loose and porous network structure of the composite electrode material is pulled apart by the strong magnetic field force. As the network structure is destroyed, its conductivity decreases. When the mass loading reaches 10 mg cm -2When the specific capacity is 1294 F g -1 (like Figure 6 As shown), at 10 A g -1 The capacity retention rate is 58.3% at the current density. Example

[0048] The NiCl in step S1 of the best embodiment 2 6H 2 O and CoCl 2 6H 2 O are mixed in a ratio of 1:1, and the other reaction conditions are the same as those in the best embodiment to obtain a nickel-cobalt nanowire electrode material.

[0049] The microstructure of the synthesized composite electrode material is basically consistent with the best embodiment. However, due to the reduction in the relative proportion of Ni element, the material has a mass loading of 10 mg cm -2 When the specific capacity is slightly reduced to 1242 F g -1 (like Figure 7 As shown), at 10 A g -1 The capacity retention rate is 64.9% at the current density. At the same time, the contact angle test shows that the material only needs 26 ms to allow the electrolyte to penetrate completely, which is only slightly longer than the best embodiment. Example

[0050] The NiCl in step S1 of the best embodiment 2 6H 2 O and CoCl 2 6H 2 O are mixed in a ratio of 3:1, and the other reaction conditions are the same as those in the best embodiment to obtain a nickel-cobalt nanowire electrode material.

[0051] The microstructure of the synthesized composite electrode material is basically consistent with the best embodiment. However, due to the decrease in the relative proportion of the Co element, the conductivity and electrochemical reaction activity of the electrode material may decrease, which directly affects the charge storage capacity. The cobalt element provides some additional reaction sites in the electrochemical reaction, which promotes the rapid insertion and detachment of ions in the electrolyte. Reducing the cobalt content will reduce these reaction sites, thereby affecting the capacitance and energy density. Through electrochemical testing, the material has a mass loading of 10 mg cm -2 When the specific capacity is reduced by 1373 F g -1 (like Figure 8 As shown), at 10 A g -1 The capacity retention rate is 57.8% at the current density. Example

[0052] The reaction temperature in step S3 of the best embodiment was changed to 35° C., and the other reaction conditions were the same as those of the best embodiment to obtain a nickel-cobalt nanowire electrode material.

[0053] When the mass loading reaches 10 mg cm -2 When the specific capacity is 1410 F g -1 (like Fig. 9 As shown), at 10 A g -1 The capacity retention rate is 66.4% at the current density. Example

[0054] The reaction temperature in step S3 of the best embodiment was changed to 45° C., and the other reaction conditions were the same as those of the best embodiment to obtain a nickel-cobalt nanowire electrode material.

[0055] When the mass loading reaches 10 mg cm -2 When the specific capacity is 1498 F g -1 (like Fig.10 As shown), at 10 A g -1 The capacity retention rate is 68.6% at the current density.

[0056] Step S1: NiCl 2 6H 2 O and CoCl 2 6H 2 O was mixed and dissolved in deionized water in a ratio of 2:1, and ultrasonically dispersed for 5 minutes to form a uniform solution A;

[0057] Step S2: Prepare 0.27 mol L -1 NaBH 4 Solution, denoted as B;

[0058] Step S3: without the effect of an external magnetic field, adding solution B into solution A and reacting at 40°C until the bubbles disappear completely, and then the reaction is terminated;

[0059] Step S4: using a magnet to separate the solution obtained in step S3 to obtain a black powder sample, and then washing it with water and ethanol;

[0060] Step S5: vacuum drying the solid powder separated in step S4 to obtain nickel-cobalt nanowire electrode material.

[0061] Figure 5 This is a scanning electron microscope image of the synthetic material under Comparative Example 1. Fig.11 It can be seen that the microstructure of the synthesized composite electrode material has serious agglomeration, which greatly hinders the transmission of ions. -2When -1 (like Fig.12 As shown), at 10 A g -1 The capacity retention rate is 30.8% at the current density.

[0062] Step S1: NiCl 2 6H 2 O and CoCl 2 6H 2 O was mixed and dissolved in deionized water in a ratio of 2:1, and ultrasonically dispersed for 5 minutes to form a uniform solution A;

[0063] Step S2: Prepare 0.27 mol L -1 NaBH 4 Solution, denoted as B;

[0064] Step S3: under the action of an alternating magnetic field with a frequency of 70 Hz, solution B is added to solution A, and the reaction is carried out at room temperature (25°C), and the reaction is terminated when the bubbles completely disappear;

[0065] Step S4: using a magnet to separate the solution obtained in step S3 to obtain a black powder sample, and then washing it with water and ethanol;

[0066] Step S5: vacuum drying the solid powder separated in step S4 to obtain nickel-cobalt nanowire electrode material.

[0067] Fig.13 This is the Brunauer-Emmett-Teller test (pore size distribution diagram) under comparative example 2. It can be seen from the figure that the undesirable specific surface area and pore structure of the material synthesized at room temperature will limit the contact area between the electrolyte and the electrode material, thereby reducing the specific capacitance. When the mass loading reaches 10 mg cm -2 When the specific capacity is 1207 F g -1 (like Fig.14 As shown), at 10 A g -1 The capacity retention rate is 48.7% at the current density.

[0068] In the above examples and comparative examples, when the mass loading reaches 10 mg cm -2 , the current density is 10 A g -1 Under different synthesis conditions, the specific capacity and capacity retention rate of the nickel-cobalt nanowire electrode material are significantly affected, as shown in Table 1 below:

[0069] Table 1

[0070] Group <![CDATA[NiCl 2 ·6H 2 O:CoCl 2 ·6H 2 O]]> Magnetic field strength (Hz) Reaction temperature (℃) <![CDATA[Specific capacitance (F g -1 ).]]> Capacity retention rate (%) Best Mode 2:1 70 40 1540 70.7 Example 1 2:1 50 40 902 57.2 Example 2 2:1 150 40 1294 58.3 Example 3 1:1 70 40 1242 64.9 Example 4 3:1 70 40 1373 57.8 Example 5 2:1 70 35 1410 66.4 Example 6 2:1 70 45 1498 68.6 Comparative Example 1 2:1 none 40 531 30.8 Comparative Example 2 2:1 70 Room temperature (25) 1207 48.7

[0071] In general, synthesis conditions such as current frequency and metal ratio have a significant impact on material properties, while the presence and intensity of an external magnetic field and a certain temperature environment are one of the key factors in achieving high-performance electrode materials.

[0072] It should be noted that the above embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of the present application.

Claims

1. A method for preparing a nickel-cobalt nanowire electrode material, characterized in that: The following steps are involved: Step S1: dissolving NiCl2·6H2O and CoCl2·6H2O in deionized water and dispersing by ultrasonic for 5 min to form a uniform solution A; Step S2: Prepare 0.2-0.3 mol L -1 NaBH4 solution, denoted as solution B; Step S3: under the action of an alternating magnetic field, adding the solution B in step S2 to the solution A formed in step S1, The reaction is carried out at a reaction temperature of 35-45°C, and the reaction is terminated after the bubbles completely disappear to obtain solution C; Step S4: using a magnet to separate the solution C obtained in step S3 to obtain a black powder sample, and washing it with water and ethanol; Step S5: vacuum drying the powder separated in step S4 to obtain nickel-cobalt nanowire electrode material.

2. The method for preparing the nickel-cobalt nanowire electrode material according to claim 1, characterized in that: The molar ratio of NiCl2·6H2O to CoCl2·6H2O in step S1 is (1:1)-(3:1).

3. The method for preparing the nickel-cobalt nanowire electrode material according to claim 1 or 2, characterized in that: The frequency of the magnetic field in step S3 is 50-150 Hz.

4. The method for preparing the nickel-cobalt nanowire electrode material according to claim 3, characterized in that: The reaction temperature in step S3 is 40°C.

5. The method for preparing the nickel-cobalt nanowire electrode material according to claim 4, characterized in that: The frequency of the magnetic field in step S3 is 70 Hz.

6. The method for preparing the nickel-cobalt nanowire electrode material according to claim 5, characterized in that: The molar ratio of NiCl2·6H2O to CoCl2·6H2O in step S1 is 2:

1.

7. A nickel-cobalt nanowire electrode material prepared according to the method according to any one of claims 1 to 6.

8. A nickel-cobalt nanowire electrode material prepared according to the method of claim 6, characterized in that: At a mass loading of 10 mg cm -2 When the electrode material has a specific capacitance of 1500 F g -1 Above 10 A g -1 The capacity retention rate at the current density is above 70%.

Citation Information

Patent Citations

  • NCS-based planar solid-state interdigital supercapacitor and preparation method thereof

    CN113871216A

  • Preparation method of supercapacitor composite electrode material

    CN117275960A